Analysis of non-compliances in the organic certification system in Turkey - Raffaele Zanoli; Danilo Gambelli; Viola Bruschi (New Medit, 2012)
Organic farming in Turkey is experiencing a strong growth in recent years, with a particular attention to export towards Europe. International and domestic trade opportunities require an efficient control system for organic products. In this paper we analyse the data from inspections of two European control bodies in Turkish farms to analyse risk patterns of non-compliance with the organic regulation. A proportion test is performed to identify the types of crops that are more likely related to non-compliant operators.
Keywords: 330; proportion test; non-compliance; Turkish organic farming